Water purification by membranes: The role of polymer science - Geise, Geoffrey M; Lee, Hae-Seung; Miller, Daniel J; Freeman, Benny D; McGrath, James E; Paul, Donald R (Journal of polymer science. Part B, Polymer physics, 2010)
Two of the greatest challenges facing the 21st century involve providing sustainable supplies of clean water and energy, two highly interrelated resources, at affordable costs. Membrane technology is expected to continue to dominate the water purification technologies owing to its energy efficiency. However, there is a need for improved membranes that have higher flux, are more selective, are less prone to various types of fouling, and are more resistant to the chemical environment, especially chlorine, of these processes. This article summarizes the nature of the global water problem and reviews the state of the art of membrane technology. Existing deficiencies of current membranes and the opportunities to resolve them with innovative polymer chemistry and physics are identified. Extensive background is provided to help the reader understand the fundamental issues involved.